Ribociclib in newly diagnosed hepatitis B infection: A case report - Di Costanzo, Fabrizio; Carrano, Simone; Iengo, Gennaro; Cefaliello, Amedeo; Cossiga, Valentina; Morisco, Filomena; Giuliano, Mario; De Angelis, Carmine; Arpino, Grazia (Frontiers in Oncology, 2023)
Breast cancer is the most frequently diagnosed cancer in women worldwide. Actually CDK4/6 inhibitor Ribociclib is approved for the treatment of metastatic hormone-positive and human epidermal growth factor receptor 2 (HER 2)-negative breast cancer, but comorbidities like infectious or cardiovascular diseases may limit its use. Case report: A 45-year-old woman was diagnosed with metastatic breast cancer in September 2021; also, her hepatitis screening resulted positive for hepatitis B infection. Patient assumed eradicative therapy for hepatitis and bit after started oncological therapy with Ribociclib. Outcome: Frequent check of hepatological function was observed since start of eradicative therapy; liver transaminases and bilirubin kept to not rise despite start of oncological treatment with Ribociclib. Patient’s Performance Status was also not compromised and revaluation at 4, 9 and 13 months showed partial response and then stable disease. Discussion: hepatotoxicity of Ribociclib is reported as a possible side effect, and often positivity for hepatitis is cause of exclusion from therapy; in our case, no hepatotoxicity was noted and patient obtained response in terms of control of both infectious and oncological diseases.